Management of Non-Tax State Revenue Management at the Technical Implementation Unit of the Lombok Embarkation Hajj Dormitory for the 2022–2024 Period - Lale Novita Ranipura; Zaenudin Mansyur; Zulpawati Zulpawati (International Journal of Social Sciences and Humanities, 2026)
This study discusses the management of Non-Tax State Revenue (Penerimaan Negara Bukan Pajak/BNBP) management at the Technical Implementation Unit of the Lombok Embarkation Hajj Dormitory for the 2022–2024 period. The main problem of this study departs from the lack of optimal utilization of Hajj Dormitory facilities outside the Hajj season, even though these facilities have great potential as a source of PNBP through the rental of buildings, lodging rooms, manasik areas, and other supporting services. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The research informants include the Head of Technical Implementation Unit (Unit Pelaksana Teknis/UPT), the Head of the PNBP Team, the PNBP Treasurer, and employees involved in the management and reporting of PNBP. The results of the study show that PNBP management is carried out through asset optimization, service quality improvement, strengthening human resources, service promotion, administrative digitalization, and cross-agency cooperation. The realization of PNBP shows an increasing trend, namely IDR 1,023,915,000 in 2022, IDR 1,936,310,000 in 2023, and IDR 2,502,870,000 in 2024. However, management still faces obstacles in the form of budget limitations, limited facilities and infrastructure, lack of socialization, public stigma that Hajj Dormitory is only for pilgrims, competition with the private sector, and limited digital innovation. This study concludes that increasing PNBP requires a professional asset management strategy, intensive digital promotion, strengthening human resources, modernizing facilities, and collaboration with various stakeholders.